Qualitative analysis of the perceptions of the training process for specialized nurses in Traditional Chinese Medicine nursing (中医护理领域内专业化护士培训过程感知的质性研究) - MENG Xuefeng (孟雪峰); CHEN Aidi (陈爱娣); WANG Hui (王惠); ZHAO Jing (赵静); ZHENG Yan (郑燕); WANG Yan (王燕); WEI Jinrong (魏金荣) (中西医结合护理)
Objective To understand the perception of the training process of specialized nurses in Traditional Chinese Medicine (TCM) nursing, and to provide ideas and basis for optimizing the training mode of TCM nursing personnel. Methods Objective sampling method was used to conduct semi-structured in-depth interviews with 22 nurses who participated in the training of TCM nurses in Jiangsu Province from August to October 2023, and the interview data were integrated and analyzed by Colaizzi seven-step analysis method. Results Three themes were extracted: the relationship between emotional change and course progress, perceived differences in professional competence, and the dilemma of application and popularization of appropriate technology of TCM nursing. Conclusion Scientific and reasonable training program can improve nurses' skills of TCM nursing and relieve the pressure during training. Personalized teaching according to the needs of nurses and help them to assess their own professional ability will help to improve nurses' professional identity of TCM nursing level and promote the promotion of appropriate techniques of TCM nursing to a certain extent. (目的 了解中医护理专业化护士培训过程的感知情况, 为优化中医护理人才培养模式提供思路和依据。方法 采用目的抽样法, 对2023年8月—10月参加江苏省中医护理专业化护士培训的22名护士进行半结构式深入访谈, 运用Colaizzi七步分析法对访谈资料进行整合与分析。结果 共提炼出3个主题: 情绪转变与培训进度间的联系, 专业能力的感知差异, 中医护理适宜技术应用和推广的困境。结论 科学合理的培训方案能提高护士的中医护理技能, 缓解培训期间的压力。根据护士的需求进行个性化教学, 帮助其进行自我专业能力的评估, 有助于提升护士的中医护理水平职业认同, 在一定程度上促进中医护理适宜技术的推广。)